Effect of Growth Media, Starter N and P Fertilizers on Growth and Yield of Tomato under Rain fed Condition in the Central Rift Valley of Ethiopia - Etissa, Edossa; Dechassa, Nigussie; Alamirew, Tena; Alemayehu, Yibekal (Journal of Agriculture and Environmental Sciences, 2019)
xperiment  was  conducted  to  evaluate  media mix  ratios  (various  soil:  sand: and  decomposed FYM proportions) and to study the effect of supplementary inorganic nitrogen (0 and 25 kg N ha-1), and phosphorous (0 and 23 kg P ha-1) for container grown tomato crop during the rainy season under field condition at Melkassa Agricultural research, Ethiopia. Three factors, namely, media proportions; supplementary N and P applications rates were combined factorially with three replications. Data on canopy characteristics such as plant height, stem diameter, main lateral branch length, canopy width, canopy depth were measured from sample plants and canopy cover (CC) was estimated. Additionally, tomato early blight was scored using the scale of 0-5 and all data were analysed using SAS. The results indicated that among the tested six media mixes, MR3 (4:1:1) produced the highest total fruit yield, followed by MR4 (3:2:1) in the form of field soil: manure: sand order. Thus, the proposed media mixes based on the results of this study is MR3 (4:1:1) that suits organic tomato production. Use of FYM further prevented crusting and sealing of the media, which is a problem associated with top soil in the Central Rift Valley area of Ethiopia. Although there was no significant difference between supplementary application of 25 kg N ha-1and no N application for container grown tomato, application of N at the rate of 25 kg ha-1was found to be better yielding. Similarly, compared to 0 kg P ha-1, application of 23 kg P ha-1 produced higher fruit yield. Although there was increase in fruit yields of tomato crop, further research is required for management of supplementary N and P fertilizer uses in container grown tomato cultivation under both rainfed and irrigated conditions